2020
DOI: 10.1016/j.vas.2019.100084
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of insulin-like growth factor 1 gene and its relationship with reproductive performances and milk yield in Sarda dairy sheep

Abstract: Highlights IGF-1 gene plays an important role in regulating reproduction in ruminants. Here three SNPs were found in the IGF-I gene in Sarda sheep. The found SNPs were related to reproductive performance and milk yield. This results could be used to improve the reproductive performances and milk yield in Sarda sheep.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…And (Deng et al, 2010) in a study on two breeds of Chinese goats (Guanzhong and Xinony saanen), with a higher percentage of GG genotype (0.64%) than AG genotype (0.36%). This is what was observed by (Sebastiano et al, 2020) in a study on Sarda sheep, where the percentage of genotypes CC 0.85 was the highest for the rest of the structures CG and GG (0.11, 0.4), respectively. And (Di Stefano., 2017) in a study on the Sarda sheep breed, the genotypes GG, AG and AA were (0.89, 0.10,0.01), respectively, while the frequency of the G allele was (0.94) and the frequency of the A allele was (0.06), and these percentages were identical to the allele ratios G and A in this study.…”
Section: Distribution Of Genotypes and Alleles Frequencies Of The Stu...supporting
confidence: 86%
See 2 more Smart Citations
“…And (Deng et al, 2010) in a study on two breeds of Chinese goats (Guanzhong and Xinony saanen), with a higher percentage of GG genotype (0.64%) than AG genotype (0.36%). This is what was observed by (Sebastiano et al, 2020) in a study on Sarda sheep, where the percentage of genotypes CC 0.85 was the highest for the rest of the structures CG and GG (0.11, 0.4), respectively. And (Di Stefano., 2017) in a study on the Sarda sheep breed, the genotypes GG, AG and AA were (0.89, 0.10,0.01), respectively, while the frequency of the G allele was (0.94) and the frequency of the A allele was (0.06), and these percentages were identical to the allele ratios G and A in this study.…”
Section: Distribution Of Genotypes and Alleles Frequencies Of The Stu...supporting
confidence: 86%
“…As these results were consistent with several studies that recorded a significant superiority of genotypes in milk production, as (Di Stefano., 2017) indicated a significant superiority (p <0.05) in 5-UTR for the daily milk production trait , as the composition outperformed The genotype GG (1.99 ± 0.52) on the GC and CC genotypes (1.64 ± 0.3, 1.58 ± 0.05) respectively in Sarda sheep. (Sebastiano et al, 2020) indicated the presence of three genotypes for the 5-UTR region (CC, CG, GG), which were significantly (P < 0.05) superior to the individuals carrying the CC genotype in three stages of daily milk production (1800, 1580 (1990) compared to the carrier individuals). This was contrary to what was observed by (Deng et al, 2010) on two Chinese goats (Guanzhong and Xinony saanen), as there were no significant differences in both genotypes GG and AG for the same region 5-UTR.…”
Section: Relationship Of the Polymorphism Of 5-utr Of Igf-1 Gene To D...mentioning
confidence: 96%
See 1 more Smart Citation
“…A similar type of polymorphism at the IGF-1 locus was discovered using the RFLP method in Egyptian small ruminant breeds, where the genotype frequencies were 53.66%, 30.49%, and 15.85% for GG, CG, and CC with allele frequencies of G (68.9%) and C (31.1%). Sebastiano et al (2020) identified allele and genotype frequencies with the SNPs method in the Sarda sheep breed at position g184028491. The result showed C and G allele frequencies were 90 and 10%, and the genotype frequencies of CC, CG, and GG were 85%, 11%, and 4%, respectively.…”
mentioning
confidence: 99%
“…Recently, Lestari et al (2020) identi ed SNP (g5752G→C) at intron 4 of IGF-I gene in Kejobong goats, where two genotypes GG and CC found to be signi cantly associated with body weight. In addition, Sebastiano et al (2020) found two SNPs at 5' UTR and exon 3 of IGF-1gene showed a signi cant association with reproductive traits and milk production in Sarda dairy sheep.…”
Section: Introductionmentioning
confidence: 92%